The Effectiveness of Using Educational Game Tools in Stimulate Smooth Motor Development to Preschooler at TKIT Bunayya Lhokseumawe - Lasmina Lumban Gaol; Odor dewi sihotang (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2022)
Excellent motor development is that the improvement of children's movements that use little muscles or solely bound body elements. Hidayat (2005) said that the development of preschool age children includes aspects of gross and excellent motor skills, language and social adaptation. The development of this aspect can be stimulated, one of which is the use of Educational Game Tools. The purpose of this research was to establish the effectiveness of using educational games to stimulate excellent motor development in preschool children at TKIT Bunayya Lhokseumawe. The method used in this research is Semi Experiment with a population of 152 TKIT Bunayya students. The sampling technique used is the Arbitrary Testing technique, with a total of 20 respondents who were given stimulation at the time of information collection. The data collection was carried out on 27 to 31 August 2018. The information from this study was processed using the dependent t-test of educational game variables and fine motor development in preschool children. The results showed that the use of educational games was effective in stimulating fine motor development in preschool children with p-esteem = 0.000 < (0.05). It is recommended to use educational game tools to stimulate motor development in children according to their developmental age. For other researchers, it is better to use other game tools to stimulate development and can develop this research with a large number of samples and have a control group.